(untitled) (Global Journal of Science Frontier Research, 2012)
A field experiment was conducted in 2009 and 2010 at the Teaching and Research Farm of the University of Agriculture, Makurdi, Benue State, Nigeria. The purpose of the experiment was to investigate the yield and yield components of newly introduced sweet potato varieties under various planting patterns with pigeonpea. Neither fertilizer nor insecticide was applied. This was done in accordance with standard practices of organic sweet potato production. The experiment was a 3 x 5 split plot set out in a randomized complete block design with three replications. Each component crop was planted at a population of 33,000 plants per ha-1 in both sole and intercropping systems. Planting pattern did not exert any significant effects on the fresh fodder weight and number of saleable tubers of sweet potato. Sole cropped sweet potato produced significantly higher number of branches per plant, tuber length and weight than row- and strip-intercropped treatments. Percentage reduction in saleable tuber yield of sweet potato varied from 47.07% (strip - intercropping) to 49.11% (row - intercropping). TIS 87/0087 and TIS 2532.OP.1.13 had significantly higher number of tubers per plant, fresh fodder weight, tuber length, circumference and weight than all other varietie . Intercropping reduced the pod weight and grain yield of pigeonpea. All intercrop combinations had land equivalent ratio figures above unity and land equivalent coefficient values greater than 0.25, except row - and strip - intercropped TIS 2532.OP.1.13, implying suitability of some of these sweet potato varieties for intercropping with pigeonpea in Makurdi.